Building Distribution and Spatial Constraints from Perspectives of Tsunami Inundation at a Small Island Context: A Study Case of Sabang-Aceh, 20 Years after the 2004 Aceh Tsunami - Syamsidik; Armaya, Hayyan Ghifarry; Suppasri, Anawat; Aulia, Fahmi; Dadek, Teuku Ahmad; Sufirmansyah; Reza, Muhammad Ichwan; Khalis, Muhammad Iqbal (Journal of the Civil Engineering Forum, 2025)
In the aftermath of the devastating 2004 Indian Ocean tsunami, the Indonesian government implemented disaster mitigation measures through improved spatial planning, particularly in settlement areas. These efforts focused on reconstruction and sustainable development strategies to enhance safety while aligning with national and regional regulations. Sabang City, located in a tsunami-prone region, was also affected by the 2004 tsunami, necessitating further evaluation of its building resilience and spatial planning. This study aims to assess the spatial distribution of buildings in Sabang City to evaluate their suitability in tsunami-prone areas and their potential for residential development. A field survey was conducted between February and June 2023, identifying and classifying 14,104 building units based on the HAZUS methodology developed by FEMA (Federal Emergency Management Agency, USA). The buildings were categorized into six structural types: Reinforced Concrete (C1-La, C1-Lb, C1-M), Concrete Frame with Unreinforced Masonry (C3-L), Steel Frame (S1-M), and Wood Frame (W1-L). Spatial analysis examined settlement patterns in relation to land capability and disaster mitigation requirements. Findings reveal significant constraints in land development for residential purposes, particularly in tsunami-prone and low-capability areas. Of the total surveyed buildings, 6,726 units (47.7%) are located in low-capability zones, primarily influenced by the dominance of protected forests and buffer zones that restrict land availability. Moreover, Sabang’s rugged topography, characterized by steep slopes and hilly terrain, exacerbates land development challenges. These findings underscore the urgent need for strategic interventions, including relocating settlements from high-risk tsunami zones, updating spatial planning policies, and integrating tsunami risk assessments into urban development strategies. Strengthening these measures will enhance urban resilience and promote sustainable growth in Sabang City.